REPRESENTASI PAKAIAN MUSLIMAH DALAM IKLAN (Analisis Semiotika Charles Sanders Peirce pada Iklan Kosmetik Wardah di Tabloid Nova) - Murti Candra Dewi (Profetik: Jurnal Komunikasi, 2013)
Since the beginning, Wardah branding their products with the halal label. Therefore, Wardah built Islamic imagine in their ads, one of way to hold the brand ambassadors dressed hijab or moslem dress. How to dress is a form of communication. Through dress, a person can convey a message to someone else. The message is used for imaging of the products Wardah. Based on this, the author are interested to examining how the representation of moslem dress in Wardah cosmetics ad.This research used a semiotic analysis of Charles Sanders Peirce to translate the meaning of the symbols in Wardah cosmetics ad. According to Peirce, semiotics set of three main elements is called triangle meaning theory (sign, object, and interpretant). The signs in the picture can be classified into icon, index, and symbol. The method used is qualitative. Qualitative research aims to explain the phenomenon with deep, through deep data collection. The results can be drawn from this research is moslem dress in Wardah Cosmetics ad represented through the use of clothing that cover the nakedness but still stylish and fashionable, so it reinforces the image of modern Islamic which was built by Wardah.